Learning Speaking Using Flash Cardboard: English as a Foreign Language Students’ Perception - Siti Wulan Asih; Ida Rahmah Andansari; Ely Widayati; Didik Murwantono (JETL (Journal of Education, Teaching and Learning), 2020)
Flash cardboard is one of the media used for speaking, especially in storytelling. Teaching by using media is very necessary for learning because it greatly influences the results of the learning process. This research wants to know English as a Foreign Language (EFL) students’ perception after they learned storytelling using flash cardboard as a media. This was phenomenological research. This research used semi-structured interviews with some students who used flash cardboard in learning storytelling. Purposive sampling was used in this research. The result shows that the student got positive impacts facilitated by the flash cardboard media, they became more confident in speaking in front of the class, they were not involved because flash cardboard helped them, students also supported speaking fluently, they can produce more than 190 words per minute (wpm) but not necessarily perfect command of intonation, vocabulary, and grammar. By using flash cardboard as the media, the media can be an alternative method in learning English specifically speaking class because it forces students to speak (really make them speak) following the target language. In the end, it can also be concluded that learning English using flash cardboard media can improve students' language skills and speaking skills. The students maintain their ability in speaking smoothly not necessarily perfect command of intonation, vocabulary, and of course the grammar. The recommendation for further study is the other researchers can add the respondents with another English skill.